Kesiapan Menikah dalam Perspektif Psikologi Pendidikan Islam - Khotimah, Anisa Nur; Mujiono, Mujiono (Lembaga Yasin AlSys, 2025)
Marriage in Islam is not merely a physical bond between two individuals but also an act of worship that encompasses spiritual, psychological, and social responsibilities. This article aims to examine the concept of marital readiness from the perspectives of Islamic religious education and educational psychology, emphasizing the importance of emotional and financial preparedness, as well as a clear understanding of roles and responsibilities within married life. Employing a qualitative approach through literature review, the study explores key dimensions of marital readiness, including moral, spiritual, physical, and psychological maturity, along with skills in conflict management, communication, and adaptation to household dynamics. The findings indicate that spiritual orientation serves as a critical predictor of marital harmony, while external support, such as family involvement and an Islamic environment, strengthens holistic preparedness. Contemporary challenges such as the childfree phenomenon, same-sex marriage, and cultural practices conflicting with Islamic teachings are highlighted as significant concerns in the discourse. The study concludes that the integration of Islamic values with educational psychology approaches is essential for cultivating comprehensive marital readiness and fostering families grounded in sakinah, mawaddah, and rahmah.